Synthesis and tribological studies of epoxidized palm stearin methyl ester as a green lubricant. (20th January 2021) - Afifah, A.N.; Syahrullail, S.; Wan Azlee, Nur Izyan; Rohah, A. Majid
Abstract: Most of the base oils used in lubricant formulations are typically derived from mineral oils, which are inherently harmful to the environment. For this reason, the aim of this study was to find an alternative base oil that can be synthesised from a renewable and biodegradable source and, most importantly, that is not a threat to the ecological environment. In this paper, palm stearin methyl ester, a local oil source, was utilised as the initial raw material in an epoxidation reaction. The oil was structurally modified at its carbon double bonds using acetic acid and hydrogen peroxide (H2 O2 ) in the presence of lipase as biocatalyst. Response surface methodology was used to investigate and optimize the effects of epoxidation variables, such as lipase concentration, temperature, and H2 O2 /acetic acid/C=C molar ratios on the relative oxirane conversion (ROC) of PSME. An optimum ROC of 98.9 ± 0.6% was obtained for the epoxidized PSME at a H2 O2 /C=C molar ratio of 1.51 mol, reaction time of 4.34 h, temperature of 52 °C, enzyme concentration of 6.416 wt%, and acetic acid/C=C molar ratio of 0.163:1. From the tribological studies, at each sliding speed and temperature condition, the produced EPSME bio lubricants consistently demonstrated lower friction coefficients and wear scar diameter values than those of PSME. The maximum reductions in COF and WSD values were found at 1200 rpm (44.5%) and 95 °C (16.6%), respectively. Graphical abstract: Image 1 Highlights: Enzymatic epoxidation of palm stearin methyl ester in a solvent-free system. Reaction temperature, lipase concentration and acetic acid/C=C molar ratio were the most significant parameters. About 97.7% conversion of double bonds into oxirane rings was achieved under optimum conditions. Epoxidized palm stearin methyl ester gave lower friction and wear values than that of a raw material. The biolubricant has a huge potential to replace the role of mineral oil in lubricant formulation.